Development of E-Interactive Module Starter System Maintenance with Discovery Learning Model - Novia Hendra; Remon Lapisa; Ambiyar Ambiyar; Wawan Purwanto (STAI Miftahul Ula Nganjuk, 2022)
The development of ICT has influenced the development of learning media that are increasingly interesting and interactive. But there are still many students who have a low enthusiasm for learning, this can be seen with the number of students who rarely attend, do not focus on learning, lack of motivation to learn. Based on the results of observations and interviews, it was found that the learning of starter system maintenance for some students is difficult to understand learning, stammering time and study space, learning is only in the form of job sheet handouts and power point slides from the teacher , students only take notes and are confused when repeating lessons at home, lack of reference sources when making assignments, low interest and motivation in learning, teacher-centered learning , students are less active and cannot measure their learning outcomes independently so that it is indispensable learning by using e-modules. This study aims to develop learning media in the form of interactive e-modules for Starter System Care with a discovery learning model that meets the validity aspects of the media. The research method used is the development (R&D) of the 4-D model, including the Define, Design, Develop and Disseminate stages, but the Disseminate stage is not carried out. The results showed validity in the validation of learning media with Validator 1 of 91%, Validator 2 of 96% and Validator 3 of 83% with an average of 90% of very valid categories. In the validation of material in the e-module, the results on Validator 1 were 9 3 %, Validator 2 96% and Validator 3 9 6% with an average of 9 5% very valid categories. Based on the results obtained, it shows that the learning media of the Starter System Care interactive e-module with the discovery learning model is feasible for students in learning.